Creating value-added services and applications for converged communications networks - Zuidweg, Han (Artech House communications and network engineering library, 2015)
This resource provides a comprehensive survey of current and emerging intelligent telecommunications networks, including underlying software, implementation, deployment, and standards. Readers are given an overview of new technologies and standards that allow operators and service providers to create and deploy value-added services in a changing world increasingly dominated by packet switched networks using the internet protocol (IP). The main goal of this book is to inform telecommunications engineers, ICT managers, and students about building applications and services over communications networks and managing them.